Leverage Factors that Impact on Company's Financial Performance - Parashtiwi, Ninggar (Ridwan Institute, 2023)
The purpose of this study is to analyze the leverage factors that affect the financial performance of the company. Leverage factors used by researchers are company size, profitability, tangible assets, and growth opportunities. The method used is a qualitative library study through the analysis of research that examines the leverage that affects the financial performance of a company. Based on the stages of data processing in this study, it was found that the results of this study indicate that leverage reduces the financial performance of a company. The company's dependence on debt as a source of financing shows that the source of funds in the form of debt has only a small impact on financial performance and tends to decrease each year. Meanwhile, leverage uses the company's assets and strengths to incur short-term and long-term costs, such as debt, to carry out the company's goal of maximizing the wealth of the company's owners.